PERANAN MAHASISWA UNIVERSITAS ISLAM NEGERI DALAM PERBAIKAN AKHLAK SANTRI DI MADRASAH - Sawaluddin Siregar; Lutfiatul Badriah Pulungan; Rizky Ramadhona; Nurlela Sri Ningsih (Yayasan Baitul Hikmah al-Zain, 2025)
The development of student behavior in madrasahs is carried out based on observations that have been carried out by the community service team at the Wadi al-Qur'an Islamic Boarding School in South Tapanuli. Findings in the field are still many students' behaviors that are not good, for example when lessons are taking place many of the students sleep in class and do not listen to the teacher during the lesson, when the teacher changes (while waiting for the teacher to come) many of them leave the class not only some people, but often all of them leave the class, even though the break time is still very long. And they often consider trivial things to be young teachers. The community service method is carried out through fostering student morals, namely, the exemplary method, the habituation method, the advice method and the punishment method. The results of community service at the Wadi Al-Qur'an Islamic Boarding School show significant changes after improving the morals of students, namely by teaching moral material to students, providing advice to students and santriyah, giving reprimands or punishments to students who have poor morals, instilling good values ​​​​towards others, especially teachers, and forming beliefs as contained in the Islamic religion.